Early quantitative infrared pupillometry for prediction of neurological outcome in patients admitted to intensive care after out-of-hospital cardiac arrest. (May 2022) - Warren, Alex; McCarthy, Ciana; Andiapen, Mervyn; Crouch, Margie; Finney, Simon; Hamilton, Simon; Jain, Ajay; Jones, Daniel; Proudfoot, Alastair
Abstract: Background: Quantitative pupillometry is recommended for neuroprognostication after out-of-hospital cardiac arrest 72 h or more after ICU admission, but the feasibility and utility of earlier assessment is unknown. Methods: This was a study of the utility of an early quantitative pupillometry index in predicting neurological outcome in patients with reduced consciousness after out-of-hospital cardiac arrest. Quantitative infrared pupillometry index was measured at 0, 6, 24, 48, and 72 h from admission. Acceptable predictive utility was defined as a positive predictive value of >95% and false positive rate of zero, with a narrow 95% confidence interval (95% CI). Results: At least one quantitative pupillometry index measurement was available from within the first 6 h for all 77 patients who met inclusion criteria. A quantitative pupillometry index ≤2.4 at baseline and ≤2.3 within the first 6 h met the criteria for utility. The positive predictive value of the baseline cut-off (≤2.4) for poor neurological outcome was 1.00 (95% CI, 0.54–1.00) with an estimated false positive rate of 0% (95% CI, 0–9%). The positive predictive value of the 6 h cut-off (≤2.3) for poor neurological outcome was 1.00 (95% CI, 0.59–1.00) with an estimated false positive rate of 0% (95% CI, 0–8%). Sensitivities of these cut-offs for ruling out poor neurological outcomes at 0 and 6 h were 19% and 22%, respectively. Of seven patients with a quantitative pupillometry index ≤2.3 within 6 h of ICU admission, none survived. Analyses that used quantitative pupillometry index measurements from 24 to 72 h, but excluded baseline and 6 h values, were not predictive by the utility criteria. Conclusions: Quantitative pupillometry within 6 h of ICU admission after out-of-hospital cardiac arrest may identify patients with a very low chance of neurologically intact survival. Further studies of early quantitative pupillometry in this population are warranted.